CHROMATOGRAPHIC BEHAVIOR AND LIPOPHILICITY OF N-(4-PHENYLSUBSTITUTED)-2,3-DIPHENYLPROPANAMIDES - Dj. Vaštag; N. Perišić-Janjić; S. Apostolov; S. Petrovic (Journal of Engineering & Processing Management, 2011)
Retention behavior of some N-(4-phenylsubstituted)-2,3-diphenylpropanamides was investigated on reversed phase thin layer chromatography (RP-C18). Retention constants of investigated compounds were determined in the following solvent systems: water-ethanol, watern-propanol and water-i-propanol. Linear relationships were obtained between retention, RM and volume fraction of organic solvent, ϕ. As a measure of lipophilicity of tested propanamides, Hansch`s lipophilicity parameter, π were calculated. Chromatography retention constants RM0 were correlated with Hansch`s lipophilicity parameter, and good linear relationships were obtained. These results confirm, that retention constants, (RM0 ), determined in reversed phase thin-layer chromatography (RP-TCL) can be used, as criteria of lipophilicity.
Keywords: Chromatography; Compound; Structure